2017
DOI: 10.1002/pmic.201600331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interacting proteins of the TaFVE protein involved in spike development in bread wheat

Abstract: WD-40 repeat-containing protein MSI4 (FVE)/MSI4 plays important roles in determining flowering time in Arabidopsis. However, its function is unexplored in wheat. In the present study, coimmunoprecipitation and nanoscale liquid chromatography coupled to MS/MS were used to identify FVE in wheat (TaFVE)-interacting or associated proteins. Altogether 89 differentially expressed proteins showed the same downregulated expression trends as TaFVE in wheat line 5660M. Among them, 62 proteins were further predicted to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…TPL colocalises with HDACs in planta (Krogan et al, 2012), but the mechanistic basis of this interaction is unknown. Interaction assays have also shown that TPL associates with homologues of proteins found in animal corepressor complexes, including HDACs, the histone‐binding protein MSI4, and CHROMATIN REMODELLING 4 (Causier et al, 2012b; Krogan et al, 2012; Zheng et al, 2017) and may also act as a bridge between AUX/IAA and the Mediator complex in auxin signalling (Ito et al, 2016). However, a definitive ‘TOPLESS complex’ remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…TPL colocalises with HDACs in planta (Krogan et al, 2012), but the mechanistic basis of this interaction is unknown. Interaction assays have also shown that TPL associates with homologues of proteins found in animal corepressor complexes, including HDACs, the histone‐binding protein MSI4, and CHROMATIN REMODELLING 4 (Causier et al, 2012b; Krogan et al, 2012; Zheng et al, 2017) and may also act as a bridge between AUX/IAA and the Mediator complex in auxin signalling (Ito et al, 2016). However, a definitive ‘TOPLESS complex’ remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The FVE protein plays important roles in determining flowering time in Arabidopsis [29]. Previous studies have shown that TaFVE directly interacts with multiple proteins to form multiple complexes that regulate the spike developmental process [30]. Those proteins included histone deacetylase, multiple chromatin-remodeling proteins, polycomb-group proteins, multiple flower development regulation factors, and flowering time control proteins.…”
Section: Identification Of Interacting Genes Of Tawus and Tawox9 Provmentioning
confidence: 99%
“…Genes related to flower development and meristem identity, SN is almost as cold tolerant as NO under short days with a delayed plant development, but is 405 less cold tolerant than NO under long days (Limin and Fowler, 2002 (VRT2), which inhibits floral meristem identity, are up-regulated by cold in barley (Trevaskis et 411 al., 2007) and wheat (Kane et al, 2005). Three MADS-box transcription factors and one (Jeon and Kim, 2011;Zheng et al, 2017). In addition, the AGAMOUS-…”
mentioning
confidence: 99%